Isolation of Major Components from the Roots of Godmania aesculifolia and Determination of Their Antifungal Activities - Tamayo Castillo, Giselle (2013)
From the methanol root extract of Godmania aesculifolia, a species selected in a multinational OAS program aimed at discovering antifungal compounds from Latin American plants, a new chavicol diglycoside (1), the known 3,4-dihydroxy-2-(3-methylbut-2-en-1-yl)-3,4-dihydronaphthalen-1(2H)-one (2), and lapachol (3) were isolated and characterized by 1D and 2D NMR and MS techniques. Only 3 exhibited fairly good activity against a panel of clinical isolates of Cryptococcus neoformans (MIC50 between 7.8 and 31.2 µg/mL) and moderate activities against Candida spp. and non-albicans Candida spp.